Age-Related Morphometric Variations of the Mandibular Canal: A Cross-Sectional Analysis using cone beam computed tomography - Shukla, Nandini; Ravi , Kumar Satish; Ghom , Savita (Journal of Neonatal Surgery, 2025)
Background: The mandibular canal houses the inferior alveolar neurovascular bundle and exhibits morphometric variations that can change with age. These differences are clinically important for various dental procedures, including implant placement, surgical interventions, and the administration of local anesthesia. Cone-Beam Computed Tomography (CBCT) provides enhanced three-dimensional visualisation relative to conventional imaging methods like orthopantomograms (OPG), rendering it an essential instrument for comprehensive morphometric analysis. Objectives-To evaluate the age-related morphometric variations of the mandibular canal using CBCT imaging. Materials and Methods: A combined total of 200 participants, comprising both males as well as females aged between the 18 and 60 years, were enrolled. CBCT scans were employed to assess the diameter and length of the mandibular canal, its positioning in relation to the buccal as well as lingual cortical plates, and the existence of anatomical variations such as bifid or trifid canals. Statistical analysis utilised SPSS software, and evaluations among different ages were executed by ANOVA, with significance established at p < 0.05. Results: A significant link exists among age as well as the length along with location of the mandibular canal (p < 0.05). The occurrence of bifid canals was noted in a subset of the research population, suggesting anatomical diversity that may affect surgical and anaesthetic results. Conclusion: Age has a significant impact on the morphometric characteristics of the mandibular canal. These findings highlight the importance of preoperative CBCT evaluation to improve the accuracy and safety of dental and maxillofacial procedures